2007
DOI: 10.1111/j.1365-2982.2007.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the placebo response in complementary and alternative medicine trials of irritable bowel syndrome

Abstract: Among patients with irritable bowel syndrome (IBS) enrolled in clinical trials of conventional medical therapy, the placebo response rate is high. IBS patients also frequently use complementary and alternative medicine (CAM), which may act through an 'enhanced placebo effect'. The purpose of this study was to estimate the magnitude of the placebo response rate in CAM trials for IBS and to identify factors that influence this response. We performed a systematic review and meta-analysis of randomized, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 82 publications
(163 reference statements)
4
71
2
2
Order By: Relevance
“…3 We agree with the complexity and the clinical relevance of this topic. Despite the evidence that most lactose malabsorbers can tolerate lactose amounts below 12 g, 4 gastrointestinal symptoms are also reported after ingestion of smaller doses of lactose.…”
Section: Lactose In Drugs: Avoided or Allowed To Lactose Maldigesters?supporting
confidence: 73%
“…3 We agree with the complexity and the clinical relevance of this topic. Despite the evidence that most lactose malabsorbers can tolerate lactose amounts below 12 g, 4 gastrointestinal symptoms are also reported after ingestion of smaller doses of lactose.…”
Section: Lactose In Drugs: Avoided or Allowed To Lactose Maldigesters?supporting
confidence: 73%
“…Dorn et al [10] performed a meta-analysis of placebo response in complementary and alternative medicine (CAM) trials in IBS. The authors performed a systematic review and meta-analysis of randomized placebo-controlled trials of CAM therapies for IBS performed between 1970 and 2006.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…Different types of therapeutic rituals activate the placebo or meaning making response in patients to varying degrees. Sometimes therapeutic rituals used in conventional and alternative treatment approaches elicit the same levels of placebo response, as found by a meta-analysis of CAM treatments for irritable bowel syndrome (Dorn et al, 2007); sometimes therapeutic rituals used in CAM approaches appear more effective than those used in conventional treatments, as found in the previously mentioned study on lower back pain (Cherkin et al, 2009); and sometimes the conventional approach yields higher placebo response rates than CAM approaches, as in Freeman et al's (2010) meta-analysis of CAM and conventional treatments for depression. The observed healing benefits of traditional medical systems such as indigenous healing practices, Ayurvedic medicine from India, Traditional Chinese Medicine, and naturopathy, have often been attributed entirely to therapeutic ritual healing (Kwan, 2007;Wampold et al, 2005), as have the observed benefits of energy-medicine techniques such as Reiki, qigong, and Therapeutic Touch (Ernst, 2006;Jonas & Chez, 2003;Martin & Henderson, 2011;Rein, 2004).…”
Section: International Journal Of Transpersonal Studies 133 Placebo Rmentioning
confidence: 75%